2012
DOI: 10.1089/neu.2011.2303
|View full text |Cite
|
Sign up to set email alerts
|

Severe Brief Pressure-Controlled Hemorrhagic Shock after Traumatic Brain Injury Exacerbates Functional Deficits and Long-Term Neuropathological Damage in Mice

Abstract: Hypotension after traumatic brain injury (TBI) worsens outcome. We published the first report of TBI plus hemorrhagic shock (HS) in mice using a volume-controlled approach and noted increased neuronal death. To rigorously control blood pressure during HS, a pressure-controlled HS model is required. Our hypothesis was that a brief, severe period of pressure-controlled HS after TBI in mice will exacerbate functional deficits and neuropathology versus TBI or HS alone. C57BL6 male mice were randomized into four gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 54 publications
4
47
1
Order By: Relevance
“…174,175 One question that is sometimes difficult to answer is whether these progressive axonal changes are the result of primarily Wallerian degeneration or moreactive secondary injury mechanisms. 31,33,[176][177][178][179] In human specimens, evidence for diffuse axonal injury throughout the corpus callosum fibers was first shown to be a common indicator of TBI.…”
Section: Diffuse Axonal Injurymentioning
confidence: 99%
“…174,175 One question that is sometimes difficult to answer is whether these progressive axonal changes are the result of primarily Wallerian degeneration or moreactive secondary injury mechanisms. 31,33,[176][177][178][179] In human specimens, evidence for diffuse axonal injury throughout the corpus callosum fibers was first shown to be a common indicator of TBI.…”
Section: Diffuse Axonal Injurymentioning
confidence: 99%
“…Previous clinical and experimental studies have shown that postinjury hypotension can exacerbate tissue damage. 72,73 For example, a recent study by Robertson and colleagues has reported that a 60-min period of hypotension (MAP reduced to 40 mm Hg), when initiated up to 1 h postinjury, significantly increases cortical contusion volume. 72 Although we have observed that guanabenz can cause a similar reduction in blood pressure in uninjured anesthetized animals (data not shown), both acute (30 min postinjury) and delayed (24 h postinjury) administration of 5.0 mg/kg of guanabenz reduced cortical tissue loss.…”
Section: Figmentioning
confidence: 99%
“…29,30 Our model is designed to be clinically relevant, mimicking a TBI sustained in the field followed by HS. It consists of three phases, including 'Shock,' 'Prehospital,' and 'Hospital.'…”
Section: Controlled Cortical Impact and Pressure Controlled Hemorrhagmentioning
confidence: 99%